Pengaruh Karakteristik Individu, Karakteristik Pekerjaan dan Karakteristik Organisasi terhadap Kepuasan Kerja Karyawan PT. Bank Rakyat Indonesia Cabang Kuala Kapuas - Deni Widanarni; Irwansyah Irwansyah; Setio Utomo (Universitas Lambung Mangkurat, 2015)
This study aimed to examine the influence of individual characteristics, job characteristics and organizational characteristics on employees’ satisfaction either simultaneously or partially. The study was conducted at PT. Bank Rakyat Indonesia Branch Kuala Kapuas. This was a quantitative approach with causal associative type. The population were all employees amounted to 41 people, and all members of the population used as samples (saturated sampling). Data were collected by using documentation, questionnaire, interview, and observation. Variables examined with Likert scale. The questionnaire first tested its validity and reliability. The data were analyzed using multiple linear regression.The research method used is quantitative research with the type of associative causal, as it will examine the influence between variables, namely the Individual Characteristics (X1), employment characteristics (X2) and Characteristics Organization (X3) influence on job satisfaction (Y).The results showed there were significant influence of Individual Characteristics, Job Characteristics, and Organizational Characteristics on Employees’ Satisfaction at PT. Bank Rakyat Indonesia Branch Kuala Kapuas both partially and simultaneously. Partially, the influence of Individual Characteristics was at 27.2%, Job Characteristics was at 22% and Organizational Characteristics was at 33.1%. Mean while, simultaneously, the influence was at 64.6%.Keywords : Individual Characteristics, Job Characteristics, Organizational Characteristics, Job Satisfaction